Omnia vincit Amor. Writing against death "Mala estrella" - Quintana Tello, Belén (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Mala estrella’s writing is a ritual that conjures death in order to meet the beloved man in poetry; as metawriting Mala estrella inquires into the power of poetry to restore sense to a lenguage and a world defeated by death.